(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article is an attept to generalize the experiences of the author in the field of teaching Economy (Macro- and Microekonomics) - gained by nearly past 40 years of didactical work (including more than 10 years at WSZiP) as well as the effects achieved in the process. The above has been supported by the theoretical knowledge taken from the sources that are perceived as archival nowadays. The Macro and Microeconomics teaching programmes intruduced have been very wide (despite potential standard limitations), this allowed the teaching team of WSZiP’s Chair of Ecomics to develop and employ practicaly all forms possible in the teaching process of the econom-ics. All forms of running classes shall not only lead to passing proper amount of know-ledge to students, but also to teach them inependent, creative thinking, as well as taking position towards received information in a productive and constructive manner. The experience shows that such approach brings evident advantages that reflect later – even if not during the first year, surely in the following years of studies.